Controls on the net dissolved organic carbon production in tropical peat - Siti Nurzakiah; Atang Sutandi; Supiandi Sabiham; Gunawan Djajakirana; Untung Sudadi (Universitas Sebelas Maret, 2020)
Soil factors such as pH and the presence of polyvalent cations can influence the net production of dissolved organic carbon (DOC). This study aimed to determine the main factors that control net DOC production. The study was conducted at Buatan Village, Siak Indrapura Regency, Riau Province, Indonesia. Soil and water sampling were done every month for a year observation, from July 2018 to June 2019. Soil sampling was carried out to determine the concentration of C-organic acids, pH, N, P, K, Cu, and soil water content (SWC). Peat water sampling was carried out using modified pore water sampling to measure DOC concentration. Groundwater level (GWL) and soil temperature were also observed. Multiple regression analysis was performed to find out the soil and environmental factors controlling the net DOC production. The results showed that the net DOC production fluctuated with seasonal changes and soil pH was a significant controlling factor (P = 0.035) and positively correlated (P = 0.040) to the net DOC production. In addition, N-mineral, PO4, and Cu were positively correlated with net DOC production (P-value: 0.026; 0.033; and 0.028; respectively) while C-organic acids and SWC were negatively correlated (P-value: 0.033; and 0.020; respectively). There was no correlation between net DOC production with GWL, soil temperature, and K concentration. This finding confirmed that pH was the main factor controlling the net DOC production and reflects DOC contribution to the solution acidity.